NEW MODELING PARADIGMS FOR PREDICTING BIRD SPECIES DISTRIBUTION - ADJAILIA Ferial; KOUACHI Ali Faiçal (My University, 2024)
Due to the ecosystem's different problems and habitat fragmentation, ecocystem monitoring becomes necessary and it is carried out by an ecological indicator. One of them is bird species and they are ideal as bioindicators and play a crucial role in ecosystems due to their sensitivity to habitat alterations, they are situated in different zones, and one of them is the riparian zone, an ecosystems located along the banks of rivers, streams, creeks, or any other water networks. It Given the importance of knowledge of species distribution for conservation and climate changemanagement, continuous and progressive evaluation of the statistical models predicting speciesdistributions is necessary.s.And the proposed dissertation comes to uncover new modelingparadigms for predicting bird species distributions and to contribute to the fields of birdconservation and ecological research. by employing sophisticated ecological modeling techniques, and spatial analysis. thereby making significant contributions to bird conservation and ecological research, This study used a multivariate synecological approach (such as, Redundancy Analysis, a variation partitioning approach based on partial RDA.. ) to analyze the relative contributions of environmental factors in forest bird community; s. The survey used the point count method to observe the spatial distribution of breeding forest birds at the end our study uncovered the most important riparian forest bird species in Medjerda River where we found significant results presence of protected, vulnerable, near threatened, endangered, and endemic bird species from 87 bird species that has been observed validates the importance of the riparian forest of Medjerda River as a crucial habitat for the preservation of rare and endemic avian species . --------------------------------------------------------------------------------------------------------------------------- نظرا لمشاكل النظام البيئي المختلفة والانقسامات التي تطرا على مواطن عيش الكائنات الحية، اصبحت مراقبة النظام البيئي ضرورية ويتم تنفيذها استنادا الى مؤشرات بيئية. أحد هذه المؤشرات هي الطيور، والتي تعتبر مثالية كمؤشرات حيوية وتلعب دو ًرا حاس ًما في النظم البيئية بسبب حساسيتها للتغيرات التي تطرا على البيئة. تتواجد في مناطق مختلفة، منها الغابات النهرية، والتي تقع على طول ضفاف األنهار والجداول وشبكات المياه األخرى. نظ ًرا ألهمية معرفة توزيع األنواعألغراض الحفاظ على البيئة وإدارة تغير المناخ، يجب تقديم تقييم مستمر وتدريجي للنماذج اإلحصائية التي تتنبأ بتوزيع األنواع. تهدف األطروحة المقترحة إلى اكتشاف نماذج جديدة للتنبؤ بتوزيع أنواع الطيور والمساهمة في مجاالت حفظها والبحث البيئي من خالل استخدام تقنيات النمذجة البيئية المتطورة والتحليل المكاني. استخدمت هذه الدراسة نه ًجا تشعبًيا متعدد المتغيرات )مثل تحليل الزيادة المتكررة، وهو نهج لتقسيم التباين استناًدا إلى تحليل الزيادة المتكررة الجزئي( لتحليل المساهمات النسبية للعوامل البيئية في مجتمع طيورالغابات النهرية. استخدمت الدراسة أسلوب العد النقطي لمراقبة التوزيع المكاني للطيور. في نهاية الدراسة، حددنا أنواع الطيور األكثر أهمية على ضفاف نهر لمجردة، حيث توجد أنواع محمية ومعرضة للخطر ومهددة باالنقراض ومحلية من بين 78 نو ًعا من الطيور التي تم رصدها، مما يؤكد أهمية الغابة النهرية على ضفاف نهر مجردة كموطن حاسم للحفاظ على أنواع الطيور النادرة والمحلية. ------------------------------------------------------------------------------------------------------------------------ Cette étude a utilisé une approche synécologique multivariée (telle que l'analyse de redondance et une approchedepartition dela variation basée surla RDA partielle)pouranalyser les contributions relatives des facteurs environnementaux dans la communauté d'oiseaux forestiers. Les relevés ont utilisé la méthode des points d'écoute pour observer la répartition spatiale des oiseaux forestiers nicheurs. À la fin, notre étude a révélé les espèces d'oiseaux des forêts riveraines les plus importantes du fleuve Medjerda, où nous avons trouvé des résultats significatifs sur la présence d'espèces d'oiseaux protégées, vulnérables, quasi menacées, en danger et endémiques parmi les 87 espèces observées. Cela valide l'importance de la forêt riveraine du fleuve Medjerda comme habitat crucial pour la préservation des espèces aviaires rareset endémiques.